MASS MOVEMENTS OF AN ALPINE ROCK GLACIER - R. Boesch; C. Graf (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
Rock glaciers, tonguelike bodies consisting of angular rock debris frozen in interstitial ice, may flow with velocities varying from a few centimeter up to several meters per year. Recent ground warming may generate an accelerated slope movement related to permafrost creep. Newer generations of commercial off-the-shelf drones like DJI Mavic are cost-effective, lightweight and still have a sufficient pay load reserve for flights at 2800 m.a.s.l. This allows that a two men crew can carry the necessary reference and drone equipment in a high alpine environment and a flight campaign can be conducted within one day. Using different cameras with similar optical resolution allows to generate DSMs with comparable accuracy. The DSM resolution should be 10 cm or better to achieve robust results. Motion tracking of rock glacier with tie point matching algorithms SIFT or SURF combined with an appropriate filter method allows to distinguish different movement patterns within local neighborhood. Compared to point-wise GPS-based methods or image-based cross-correlation approaches, tie point matching allows to detect inhomogeneous movement patterns, which are typical for rock glaciers in a high alpine environment.